2017
DOI: 10.1002/gcc.22448
|View full text |Cite
|
Sign up to set email alerts
|

Candidate susceptibility variants for esophageal squamous cell carcinoma

Abstract: Esophageal cancer is common worldwide, and often fatal. The major histological subtype is esophageal squamous cell carcinoma (ESCC). ESCC shows familial aggregation and high heritability. Mutations in RHBDF2 cause tylosis, a very rare disorder characterized by high life-time risk of ESCC, but no other well-established predisposition genes have been identified. To identify candidate susceptibility variants for ESCC we utilized the Population Information System and the Finnish cancer registry to find study mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…46 Furthermore, another study investigating susceptibility variants for oesophageal SCC reported missense variants in DDOST in two cases. 47 The mechanism whereby DDOST permits metastasis is unclear, but it may involve protein glycosylation and the impact of this via various biological processes relevant to cancer. 48 For example, DDOST functions as a subunit for an accessory protein required for stabilization of the STT3 protein subunits of oligosaccharyltransferase (OST), 49,50 which promotes tumour immune evasion via PD ligand 1 (PD-L1).…”
Section: Discussionmentioning
confidence: 99%
“…46 Furthermore, another study investigating susceptibility variants for oesophageal SCC reported missense variants in DDOST in two cases. 47 The mechanism whereby DDOST permits metastasis is unclear, but it may involve protein glycosylation and the impact of this via various biological processes relevant to cancer. 48 For example, DDOST functions as a subunit for an accessory protein required for stabilization of the STT3 protein subunits of oligosaccharyltransferase (OST), 49,50 which promotes tumour immune evasion via PD ligand 1 (PD-L1).…”
Section: Discussionmentioning
confidence: 99%
“…For a brief description of the pipeline used on the raw sequencing data, please refer to Donner et al 2017 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly inactivating mutations clustered in defined geographic areas, being more frequent in those ECSSs which affect North American patients than in those aroused in Chinese population. Moreover, germline mutations in the RHBDF2 gene (17q25) which cause tylosis (focal non-epidermolytic palmoplantar keratoderma) have been reported to be markers of genetic familial susceptibility for the early onset of ESSC [ 49 , 50 , 51 ].…”
Section: Main Mutational Patterns and Regulatory Networkmentioning
confidence: 99%